Teachers’ Teaching Strategies in Activating Students’ Participation in Learning English : A Study in Junior High School 1 Gangga, North Lombok Regency - Andjani, Jessica Tamia; Waluyo, Untung; Soepriyanti, Henny; Amin, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Student participation in English as Foreign Language (EFL) classrooms remains a significant challenge in rural Indonesian schools, where barriers such as low motivation, limited vocabulary, and lack of confidence hinder active engagement. This study investigates teaching strategies employed by two English teachers, TG and YF, at Junior High School 1 Gangga to address these issues. The objectives of the research are to identify the strategies used by the teachers, explore the challenges they face in activating student participation, and examine their perceptions of classroom engagement. A qualitative case study design was utilized, employing semi-structured interviews, classroom observations, and document analysis as data collection methods. Thematic analysis was applied to identify patterns and themes within the data. The findings reveal that both teachers employed differentiated learning, group discussions, reading aloud, and English games as key strategies to enhance student participation. However, challenges such as resource limitations, varying student proficiency levels, and low confidence levels were consistently reported. To address these, the teachers adapted their strategies by leveraging available resources, conducting personalized assessments, and fostering a supportive learning environment. The study underscores the importance of teacher flexibility and creativity in overcoming barriers to student participation. Its implications suggest the need for professional development programs to equip teachers with innovative strategies and improved resource allocation to support effective teaching in similar EFL contexts. These findings contribute to the broader discourse on enhancing EFL learning outcomes in under-resourced settings.